2013
DOI: 10.1091/mbc.e13-06-0333
|View full text |Cite
|
Sign up to set email alerts
|

The Rac-GAP Bcr is a novel regulator of the Par complex that controls cell polarity

Abstract: The Par complex (Par3, Par6, and PKCζ) controls cell polarity, which is essential for many biological processes. Here we identify the Rac1 GTPase-activating protein Bcr as an integral member of the Par complex that regulates polarized cell migration by locally restricting both Rac1 and PKCζ function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…This function contrasts with the activity of RhoA, which is involved in the formation of stress fibers and cell contraction (Kong et al, 2013;Narayanan et al, 2013). However, advanced imaging methods used to study Rho GTPase activation have demonstrated a more complex, time-dependent phenotype that generally remains controversial in the Rho GTPase field (Pertz, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This function contrasts with the activity of RhoA, which is involved in the formation of stress fibers and cell contraction (Kong et al, 2013;Narayanan et al, 2013). However, advanced imaging methods used to study Rho GTPase activation have demonstrated a more complex, time-dependent phenotype that generally remains controversial in the Rho GTPase field (Pertz, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This process requires the activation of Rho GTPase proteins, which finely regulate the actin cytoskeleton (Kong et al, 2013;Narayanan et al, 2013;Villarreal et al, 2014). The rearrangement of the actin cytoskeleton and the generation of a wavy extension of the cell membrane called a lamellipodium during astrocytic stellation are directed by Rac1 (Bustelo et al, 2007;Ellenbroek et al, 2012;Racchetti et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that Bcr interacts with Tiam1 and members of the partition-defective (Par) polarity complex in cortical astrocytes [28]. The Par complex, composed of Par3, Par6, and atypical protein kinase Cζ (PKCζ), controls cell polarization in many different contexts, including directional cell migration, axon specification, and spine morphogenesis [29].…”
Section: Multidimensional Regulation Of Single Rho Gtpasesmentioning
confidence: 99%
“…The Par complex functions in part by recruiting Tiam1 to specialized sites where it promotes local Rac1 activation [30]. We found that Bcr also associates with the Par complex and that Bcr loss in astrocytes leads to faster, more random migration and striking polarity defects in cytoskeletal organization and centrosome orientation [28]. These defects are caused by misregulation of both Rac1 and PKCζ and are rescued by wild-type Bcr, but not by a Bcr mutant that cannot associate with the Par-Tiam1 complex [28].…”
Section: Multidimensional Regulation Of Single Rho Gtpasesmentioning
confidence: 99%
“…4.4.8). Furthermore in mammalian cells, through its inhibition of aPKC, Lgl is linked to the regulation of Tiam1 (a Rac1-GEF) and activation of the Rac1-GTPase, which has roles in tight junction formation, dendritic spine morphogenesis and cell migration (Chen and Macara 2005;Mertens et al 2005;Zhang and Macara 2006;Narayanan et al 2013;Wang et al 2012), and also the JNK or p38 stress response pathways (Lambert et al 2002;Buchsbaum et al 2002).…”
Section: The Actin Cytoskeletonmentioning
confidence: 99%